Multi-criteria Decision Making to Improve Displacement Amplification Ratio of an Amplifying Compliant Mechanism Flexure Hinge - Huynh, Ngoc Thai; Huynh, Van Nam; Tran, Quoc Nhiem; Phan, Chi Bao; Vu, Minh Hung; Nguyen, Trieu Khoa; Nguyen, Quoc Manh (Directorate for Research and Community Services, Institut Teknologi Bandung, 2025)
Multi-criteria decision-making methods including the Extended Additive Ratio Assessment (EAMR), Simple Additive Weighting (SAW), Weighted Aggregated Sum Product Assessment (WASPAS), and Evaluation based on Distance from Average Solution (EDAS) were employed in conjunction with the Taguchi method and finite element method (FEM) to optimize the displacement amplification of an amplifying compliant mechanism utilizing flexure joints. Initially, design variables for the compliant mechanism amplifier were selected. Minitab software was utilized to generate 27 experimental scenarios, and SolidWorks was employed to design 27 models of compliant mechanisms amplifier with flexure hinges. The stress and displacement of each design were estimated by FEM in ANSYS. The optimal mechanism was identified based on the largest displacement criterion as well as ensuring the smallest stress, as determined through the multi-criteria decision-making techniques and validated using the Taguchi method, variance analysis, and 3D surface plots. The predicted outcomes from the optimization methods are compared with FEM results for verification. For the EAMR method, the predicted and optimal values are 0.742046 and 0.74968, respectively. The SAW method yields values of 0.88684 (predicted) and 0.89210 (optimal), while the WASPAS method produces 0.8432 and 0.8481. The EDAS method results are 0.7978 (predicted) and 0.8187 (optimal). For displacement (Di), the predicted and optimal values are 0.65269 and 0.65238, respectively, and for stress (St), they are 49.3398 and 48.7950. In all methods, the deviation between predicted and optimal values remains under 3%. The resulting displacement amplification ratio (DAR) of the final mechanism is 65,237.